Sustainability of Social, Economic, and Institutional Aspects on Fisheries Management: Case Study at Palabuhanratu Nusantara Fishing Port, West Java - Agustian, Dita; Megantara, Erri Noviar; Ihsan, Yudi Nurul; Cahyandito, Martha Fani (Faculty of Fisheries and Marine Science, Brawijaya University, 2023)
Social, economic, and institutional aspects are crucial for supporting sustainable fisheries management. The objective of this research is to assess the level of sustainability of the social, economic, and institutional aspects of fisheries management, especially at the fishing port level. In this research, field research was conducted using composite analysis and flag modelling visualization in the Ecosystem Approach to Fisheries Management (EAFM) as a tool to assess the sustainability of each aspect. Data were obtained from interviews and questionnaires answered by 90 respondents, including fishermen, port officers, and fisheries entrepreneurs in the Palabuhanratu Nusantara Fishing Port. The results showed that, overall, the sustainability condition in the social aspect was good with a score of 79.69, while the economic aspect was moderate with a score of 55.32, and the institutional aspect was good with a score of 80.28. The lowest levels of sustainability in the social and economic aspects were found in the indicators of stakeholder participation and fishery household income, both in the medium category. In the institutional aspect, the lowest level of sustainability was found in the indicator of compliance with responsible fisheries management principles, which was in the good category. These results are expected to provide stakeholders with the necessary information to take corrective steps to improve sustainability in fisheries management, particularly in the social and economic aspects.